Hungarian Monitoring, 23 May 1990 . [Magyar rádiófigyelő], 1990. május 23 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Railways strike in Poland - Economic reform in the USSR Domestic Affairs: - Oath of the new Hungarian government - Parliamentary debate of the government program - Negotiations start about the mutual visa waiver agreements with Switzerland Economy: - Mátyás Szűrös opened the Budapest International Fair - Opel talks in Hungary Külpolitika: - Lengyel vasutassztrájk - Szovjet gazdasági átalakítás Belpolitika: - Letette esküjét az új magyar kormány - A kormányprogram parlamenti vitája - Tárgyalás kezdődhet a kölcsönös vízumkötelezettség eltörléséről Svájccal Gazdaság: - Szűrös Mátyás megnyitja a BNV-t - Magyarországon tárgyal az Opel